Pengaruh Penggunaan Mulsa Alang-Alang, Kenikir dan Kirinyu terhadap Pertumbuhan dan Hasil Bawang Merah Di Tanah Mediteran pada Musim Penghujan - Mulyono Mulyono (Universitas Muhammadiyah Yogyakarta, 2015)
The study was held inSimo village, Boyolali, Central Java.The study used field experiments with a single factor that arranged in randomized completely block design.The treatments were control (P0), Alang-alang as mulch (P1), Kirinyu as mulch (P2), and Kenikir as mulch (P3), each treatment was repeated three times.The parameters were plant height, number of leaf, fresh weight of plant, dry weight of plant, number of tuberper hill, weight of tuber per hill, yield, fresh weight and dry weight of weeds. The results showed that mulch grass, kirinyu and kenikir was not significantly affect plant height, leaf number, number of tubers per hill and yield per hectare.Mulching grass, and kenikir kirinyu affected on plant fresh weight, dry weight and plant weight of tubers per hill.Mulching kenikir improved the plant fresh weight, dry weight of plants and weight of tubers per hill.Morover, Alang-alang, Kirinyu, and Kenikir as organic mulch significanly decreased the growth and abundant of weed and improved the growth of shallot plant. Alang-alang was the most highest decreasing the growth of weed.